The Influence of Discipline and Body Fitness to The Performance of Physical Education Teachers - Asrianti, Asrianti; Tangkudung, James; Dlis, Firmansyah; Asmawi, Mochammad; Hanif, Achmad Sofyan; Muchtar, Jufrianis (Journal of Education, Health and Sport, 2020)
The purpose of this study was to determine the effect of discipline and physical fitness on the performance of physical education teachers. This study uses the path analysis method. This research to find the direct effect between variables discipline and physical fitness on the work of physical education teachers. The sample used 102 certified physical education teachers in the province of Southeast Sulawesi. Discipline and performance are measured using questionnaires that have been validated by experts. Physical fitness is measured by using five items of fitness tests namely body lift test for men and elbow bend for girls, sit-ups, push-ups running back and forth and also endurance that is running with a distance of 2.4 km. Data analysis technique used path analysis. The finding of the variable such as, 1) discipline variable (X2) has a direct positive effect on teacher performance (Y), amounting to (R2 = 0.160). 2) physical fitness variable (X3) has a direct positive effect on teacher performance (Y), amounting to (R2 = 0.376), 3) discipline variable (X2) has a direct positive effect on physical fitness (X3), amounting to (R2 = 0.889). Based on the two independent variables that gave the greatest contribution to improving the performance of physical education teachers was physical fitness (R2 = 0.376). In this case a teacher who has good physical fitness will also have good performance.